Education and Politics in Africa - GRIBANOVA Valentina Valerevna (Ученые записки Института Африки Российской академии наук)
The article is devoted to the characterization of the models and the stages of formation of education systems in African countries and of their current status. The aim of the work was to analyze the impact of various factors on the development of education in Africa. In particular, the impact of military conflicts and the activities of terrorist organizations on the field of education were investigated. It also analyzes the increasing role of the world community in the development of education in African countries in recent decades. The main examples are the aspects of the activities of the terrorist organization Boko Haram, aimed at destabilizing and directly destroying the education system of Nigeria, and the impact of the Mali conflict of 2012-2013 on education. The activities of Boko Haram are widely covered in the scientific literature, but the article focuses on its aspects that are connected precisely with the negative impact on the educational system in Nigeria. The work broadens the perception of the challenges currently facing educational systems in Africa.